MODEL PEMBIAYAAN PENDIDIKAN BERKELANJUTAN: ANALISIS TERHADAP PENERAPAN MODEL BUILD-OPERATE-TRANSFER (BOT) PADA INFRASTRUKTUR PENDIDIKAN DI PERGURUAN TINGGI - Samiyono; Sofwan Manaf; Rokimin; Fajar Suryono (Irfani, 2025)
ABSTRACT The implementation of the Build-Operate-Transfer (BOT) model in educational infrastructure development at Indonesian universities has had a significant impact on the quality of educational facilities and resource management. This model involves the private sector in the financing, construction, operation, and management of educational facilities, aiming to reduce dependence on government funding. This study aims to analyze the mechanisms of implementing the BOT model in Indonesian universities, the challenges faced, and its impact on the quality of educational infrastructure and student learning experiences. The method used in this study was a qualitative approach using in-depth interviews and document analysis from various parties involved in BOT projects at universities. The results indicate that the BOT model is effective in improving educational infrastructure by reducing the burden on the public budget and improving the quality of facilities that support learning activities. However, key challenges in implementing this model include financing, risk management, and coordination between relevant parties. The successful implementation of the BOT model depends on careful planning, clear communication between the private sector, the government, and universities, and stable regulations that support private investment. In addition, careful risk management and the use of educational technology such as a Learning Management System (LMS) contribute positively to the student learning experience. This study concludes that implementing the BOT model can provide a long-term solution to address educational infrastructure deficiencies in Indonesia. However, its success requires close collaboration between the public and private sectors. Transparent management and proper planning will ensure that the BOT model can contribute to improving the quality of higher education in Indonesia, supporting the development of student competencies in this digital era.